Shift and Metabolic Potentials of Microbial Eukaryotic Communities Across the Full Depths of the Mariana Trench - Zhu, Xiao-Yu; Liu, Jiwen; Xue, Chun-Xu; Tian, Jiwei; Zhang, Xiao-Hua (Frontiers in Microbiology, 2021)
Microbial eukaryotes are widespread and play important roles in marine ecosystems. However, their ecological characteristics in the deep sea (> 1,000 m), especially hadal trenches, were largely unknown. Here, we investigated the diversity and metabolic potentials of microbial eukaryotes along the whole water column of the Mariana Trench by metagenomics. Our results showed clear depth-related distribution of microbial eukaryotic community and associated metabolic potentials. Surface seawater was dominated by phototrophic/mixotrophic groups (e.g., Dinoflagellata) and genes involved in biosynthesis (photosynthesis and fatty acid biosynthesis), while deep (bathypelagic and/or hadal) seawaters were enriched with heterotrophic groups (e.g., Bicoecea) and genes related to digestion (lysosomal enzymes and V-type ATPase) and carbohydrate metabolism. Co-occurrence analysis revealed high intra-domain connectivity, indicating that microbial eukaryotic composition was more influenced by microbial eukaryotes themselves than bacteria. Increased abundance of genes associated with unsaturated fatty acid biosynthesis likely plays a role in resisting high hydrostatic pressure. Top1 and hupB genes, responsible for the formation and stabilization of DNA structure, were unique and abundant in the hadal zone and thus may be helpful to stabilize DNA structure in the deep sea. Overall, our results provide insights into the distribution and potential adaptability of microbial eukaryotes in the hadal zone.